Pancalogi of Integrative Elderly Islamic Education Based on Tasawuf-Ecospiritualism - Husna Nashihin; Muhammad Sularno; M. Daud Yahya; Zulkifli Musthan; Noor Aziz (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is driven by an increase in the percentage of the elderly in 2019 by 9.6% of the total 25 million populations in Indonesia, and is predicted to increase by 13.24% in 2025. This reality is directly proportional to the increasing problems of elderly life, so it needs to be an improvement in the elderly Islamic education model as a solution. This study is categorized as literary research, which uses qualitative analysis. This study uses a context analysis model in order to obtain a contextual interpretation of literary data. The data sources of this study consist of books and scientific journals about Islamic education by Muhammad Jawwad Ridla, Yusuf Qardhawi, Seyeed Hossein Nasr, and Omar Muhammad Al Toumy Al Syaibani; on Psychology of the Elderly by Kimmel Dougles, Berger and Luckman, Hurlock, Skinner, Berk, Havighurst, Mönks, Ericson, and Partini Suardiman; on Contextual Tasawuf by Annemarie Schimmel; and on Ecospiritualism by Nawal Amar. This study shows that, according to Husna Nashihin, the pancalogi of integrative Islamic education for the elderly based on tasawuf-ecospiritualism includes aspects of spirituality, psychology, socio-cultural, health, and economics of the elderly. The description of the pancalogi of elderly Islamic education includes 16 (sixteen) sub aspects of elderly development and 14 (fourteen) elderly Islamic education curriculum materials.